Computing Simulation of Post-buckling in Functionally Graded Materials - A Review - Elias Randjbaran; Rizal Zahari; Ramin Vaghei (Institute of Advanced Engineering and Science, 2014)
A review on the recent development in the non-linear flutter and thermal buckling of an FGM panel under the combined effect of elevated temperature conditions and aerodynamic loading is investigated using a finite element model based on the thin plate theory and von Karman strain-displacement relations to account for moderately large deflection. The governing non-linear equations are obtained using the principal of virtual work adopting an approach based on the thermal strain being a cumulative physical quantity to account for temperature dependent material properties. This system of non-linear equations is solved by Newton–Raphson numerical technique. It is found that the temperature increase has an adverse effect on the FGM panel flutter characteristics through decreasing the critical dynamic pressure. Decreasing the volume fraction enhances flutter characteristics but this is limited by structural integrity aspect. Structural finite element analysis has been employed to determine the FGM panel's adaptive response while under the influence of a uniaxial compressive load in excess of its critical buckling value. It is shown that, utilising the considerable control authority generated, even for a small actuator volume fraction, the out-of-plane displacement of the post-buckled FGM panel's can be significantly reduced. http://dx.doi.org/10.11591/telkomnika.v12i12.6672